PENGUKURAN MATURITY LEVEL TATA KELOLA TI BERDASARKAN TUJUH KERANGKA KERJA COBIT 4.1 - Irmawati Carolina (Universitas Bina Sarana Informatika Kota Sukabumi, 2016)
Role of IT in business is very big because affects the continuity of operational processes oforganizations. In its management, IT needs a standard that can help managers to see the gapsbetween business risks, control needs, and problems. In its management, IT needs a standard thatcan help managers to see the gaps between business risks, control needs, and problems of existingtechniques. IT Governance is a structure of relationships and processes that drive and manage theorganization in achieving its objectives by providing value-added of IT utilization and balancingrisk with the results provided by IT and processes. Maharaja Ban is a company that is committedto developing business and serving the needs of customers, so it needs the support of good ITGovernance. COBIT (Control Objectives for Information and Related Technology) is one tool inthe measurement of IT Governance that is used to view existing IT governance. COBIT has 4domains, namely Plan and Organization (PO), Acquisition and Implementation (AI), Delivery andSupport (DS), and Monitoring and Evaluate (ME). This research was conducted for the fourthdomain is the restriction on the 7 process . Research results found that the level of maturity(maturity level) IT Governance at Maharaja Ban on level 1. This means that the current maturitylevel was below the expected level of maturity, so it needs to be improved to be located at theexpected level. To overcome the existing gap in this research has recommended several steps thatmust be done.